Estructura factorial de la Cardiff Anomalous Perceptions Scale (CAPS) en una muestra de población colombiana (2015)
The continuum hypothesis of psychosis assumes that hallucinations are not exclusive of psychotic disorders. A number of psychometric tests have been developed to assess psychosis using a dimensional model.